2004
DOI: 10.1099/vir.0.19637-0
|View full text |Cite
|
Sign up to set email alerts
|

Classical swine fever virus induces proinflammatory cytokines and tissue factor expression and inhibits apoptosis and interferon synthesis during the establishment of long-term infection of porcine vascular endothelial cells

Abstract: Infection with virulent strains of classical swine fever virus (CSFV) results in an acute haemorrhagic disease of pigs, characterized by disseminated intravascular coagulation, thrombocytopenia and immunosuppression, whereas for less virulent isolates infection can become chronic. In view of the haemorrhagic pathology of the disease, the effects of the virus on vascular endothelial cells was studied by using relative quantitative PCR and ELISA. Following infection, there was an initial and short-lived increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 28 publications
5
94
0
1
Order By: Relevance
“…Other in vitro investigations showed that CSFV also disrupted secretion of IFN-α and proinflammatory cytokines in porcine aortic and kidney endothelial cell lines [7,11]. It is to emphasize that CSFV-infected mo-DC were able to mature only when TNF-α and IFN-α were added into culture medium [13].…”
Section: Discussionmentioning
confidence: 94%
“…Other in vitro investigations showed that CSFV also disrupted secretion of IFN-α and proinflammatory cytokines in porcine aortic and kidney endothelial cell lines [7,11]. It is to emphasize that CSFV-infected mo-DC were able to mature only when TNF-α and IFN-α were added into culture medium [13].…”
Section: Discussionmentioning
confidence: 94%
“…The presence of an apoptosis-resistant, infected cell population, such as endothelial cells, is consistent with the high viral loads detected in acutely infected animals. Endothelial cells are important immune modulators (Bensaude et al, 2004;Campos et al, 2004) and so infection of these cells is likely to play a key role in the immunosuppressant and haemorrhagic effects of CSFV.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was found that CSFV infection of primary porcine endothelial cells could counteract the pro-apoptotic effects of the dsRNA mimic pIpC (Bensaude et al, 2004). However, little was known concerning the mechanistic aspects of this process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations